Advances in the understanding and therapeutic manipulation of cancer immune responsiveness: a Society for Immunotherapy of Cancer (SITC) review - Francesco M Marincola; Alessandra Cesano; Yana G Najjar; Davide Bedognetti; Marco Ruella; Sarah Warren; Christine Spencer; Elad Ziv; Tomas Kirchhoff; Jennifer McQuade; Tullia C Bruno; Jakob Nikolas Kather; et al. (Journal for ImmunoTherapy of Cancer)
Cancer immunotherapy—including immune checkpoint inhibition (ICI) and adoptive cell therapy (ACT)—has become a standard, potentially curative treatment for a subset of advanced solid and liquid tumors. However, most patients with cancer do not benefit from the rapidly evolving improvements in the understanding of principal mechanisms determining cancer immune responsiveness (CIR); including patient-specific genetically determined and acquired factors, as well as intrinsic cancer cell biology. Though CIR is multifactorial, fundamental concepts are emerging that should be considered for the design of novel therapeutic strategies and related clinical studies. Recent advancements as well as novel approaches to address the limitations of current treatments are discussed here, with a specific focus on ICI and ACT.